Correlation between serum vitamin C level and COPD assessment test score in chronic obstructive pulmonary disease patients - Cipuk Muhaswitri; Drupadi Dillon; Jamal Zaini (World Nutrition Journal, 2020)
Background: COPD is a disease due to oxidative stress causing low pulmonary function, resulting in low quality of life. A standard test to measure the quality of life in COPD is COPD Assessment Test (CAT). Vitamin C as antioxidant is widely available in the pulmonary epithelial fluid.  This study aimed to investigate the correlation between serum vitamin C level and CAT score in COPD.Methods: This cross-sectional study was conducted at Persahabatan Hospital, East Jakarta, involving 47 subjects using consecutive sampling method. Interview was used to assess subjects’ characteristics and vitamin C intake using semi-quantitative FFQ. Clinical classification, lung function, comorbidity, and CAT scores were gathered from medical records or interview. BMI was used to determine nutritional status, while vitamin C serum level was assessed using spectrophotometry. Results and conclusions: All subjects were male, mean age was 66.6 years, mostly ex-heavy  smokers, with decreased lung function, and 25% were undernourished. Vitamin C intake was sufficient, but low in serum vitamin C level and CAT score.There was no correlation between serum vitamin C level and CAT score.